Towards quality consumption: Segmentation of the Hungarian wine market based on wine consumption and purchasing habits. Issue 4 (2nd September 2019) - Hlédik, Erika; Harsányi, Dávid
Abstract : Purpose: Hungarian wine culture has been developing steadily over the past decades. The number of wineries offering quality wine is growing as consumer interest in quality consumption increases. The purpose of this paper is to study the segmentation of the Hungarian wine consumers based on their purchase habits and preferences to identify how this shift towards quality consumption is represented in these segments. Design/methodology/approach: An online survey was conducted in Hungary. Nearly 28, 000 consumers filled in the questionnaire. The TwoStep Cluster analysis could handle the large database and variables measured on different measurement scales. Findings: The growing interest towards quality wine in the market is reflected in the study's segmentation results. The large sample size made it possible to identify a special Hungarian wine consumer group, which has different buying habits than traditional wine consumer segments. Four segments were evolved: ordinary wine consumers, unsophisticated wine consumers, wealthy wine-experts and open-minded consumers. The last two segments seem to be the most valuable groups for high-quality wine producers. Originality/value: The sample size allowed a relatively novel segmentation, whereby the preferences and purchasing habits of smaller, high-quality wine consumer groups became measurable.